Gastric Trichobezoar with Rapunzel Syndrome: A Case Report - Anoop Dixit; Mohd Arshad Raza; Rohit Tiwari (Journal of Clinical and Diagnostic Research, 2016)
Bezoars are collections of non-digestible matter that usually accumulates in stomach and can extend to small bowel. Trichobezoars (concretions of hair) are unusual and are usually found in young psychiatric females, who often deny eating their own hair (trichophagy). We are presenting a case of gastric trichobezoar with a long thin tail in a 20 years young female with a history of trichophagia. Patient was managed by exploratory laparotomy and anterior gastrotomy. Postoperatively she recovered well and was discharged in satisfactory condition with advice for psychiatric follow-up.